The influence of technostress, work–family conflict, and perceived organisational support on workplace flourishing amidst COVID-19 - Harunavamwe, Martha; Ward, Chené (Frontiers in Psychology, 2022)
This study used a model to determine the combined effect of technostress, work-family conflict and perceived organisational support on workplace flourishing for employees in the higher education. A descriptive quantitative research framework was adopted; data were collected from a sample of 227 academic and support staff employees from a selected University in South Africa. The results indicated that technostress through perceived organizational support and through work family conflict influence workplace flourishing. No direct significant effect was reported between technostress and workplace flourishing. Technostress, perceived organizational support and work family conflict combined explained 47% of variance in work place flourishing. Perceived organizational support have the strongest direct influence on workplace flourishing, and technostress is a strong determinant of work family conflict which mediate the relationship between technostress and workplace flourishing. The study concluded that providing organizational support and creating work life balance favorable policies assist employees to manage technostress better and enhance workplace flourishing. The results indicate that in the remote working context, though employees struggle with demands imposed by techno invasion and techno complexity, perceived organizational support and balanced work life act as job resources that enhance emotional, psychological and social wellbeing (workplace flourishing).